Auroral Heating of Plasma Patches Due to High‐Latitude Reconnection. Issue 12 (7th December 2021) - Díaz Peña, Joaquín; Semeter, Joshua; Nishimura, Yukitoshi; Varney, Roger; Reimer, Ashton; Hairston, Marc; Zettergren, Matthew; Hirsch, Michael; Verkhoglyadova, Olga; Hosokawa, Keisuke; Shiokawa, Kazuo
Abstract: This study exploits the volumetric sampling capabilities of the Resolute Bay Incoherent Scatter Radar (RISR‐N) in collaboration with all‐sky imagery and in situ measurements to examine the interplay between cold plasma transport and auroral precipitation during a high‐latitude lobe reconnection event on the dawn side. Solar wind IMF preceding the event was characterized by an impulsive negative excursion in B z embedded within a period of B z  > 0 and B y  < 0. The combined effects of transport and magnetic stress release associated with a high‐latitude reconnection pulse drove a co‐mingling between patches and soft electron precipitation, creating common regions of elevated electron density and temperature. Vertical ionospheric profiles extracted in the rest frame of the drifting patch showed a contemporaneous increase in T e above 200 km and N e below 250 km while at the same time showing only a small impact in N e near the F‐region peak. The observations suggest a new mechanism for creating a "hot patch" wherein the density enhancement is not generated by the precipitation but is warmed by it. The physics‐based GEMINI model was used to explore the response to the observed precipitation as a function of altitude and time. Model results suggest that a correlated enhancement in N e and T e at DMSP altitudes (∼800 km), that is, hot patch, can be produced by auroral heating and upward diffusion, irrespective of lower altitude density structure. The study highlights the need for densely distributed observations in space and time for understanding both mesoscale and small‐scale ionospheric dynamics in regions subject to complex forcing. Key Points: Observations by RISR‐N reveal a co‐mingling of cold patches and a transpolar arc, creating a region of elevated Ne and Te ("hot patch") The combination of transport and soft precipitation is a signature of lobe reconnection and suggests a new mechanism for hot patch generation Numerical modeling of the event predicts an enhancement in Ne and Te at DMSP altitudes due to diffusion, not the presence of a patch